2008
DOI: 10.1177/0269215508089058
|View full text |Cite
|
Sign up to set email alerts
|

A phase II exploratory cluster randomized controlled trial of a group mobility training and staff education intervention to promote urinary continence in UK care homes

Abstract: Group mobility training and staff education to promote continence is feasible and acceptable for use with care home residents, including those with cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 25 publications
4
56
0
Order By: Relevance
“…49 The unadjusted ICC for the BI measure in the present trial was 0.36 at baseline and 0.10 for baseline to 3 months. After allowing for the effect of the treatment arm, TACs and type of care home, the ICC for the primary BI measure reduced to 0.09 (95% CI 0.05 to 0.17).…”
Section: Intracluster Correlation Coefficientmentioning
confidence: 49%
See 3 more Smart Citations
“…49 The unadjusted ICC for the BI measure in the present trial was 0.36 at baseline and 0.10 for baseline to 3 months. After allowing for the effect of the treatment arm, TACs and type of care home, the ICC for the primary BI measure reduced to 0.09 (95% CI 0.05 to 0.17).…”
Section: Intracluster Correlation Coefficientmentioning
confidence: 49%
“…79 Furthermore, the BI was used in previous studies assessing the efficacy of OT, and the data from our study are suitable to be incorporated into meta-analyses. 34,48,49 For pragmatic reasons, we chose to use the shortened BI scale between 0 and 20. 77 A higher score signifies that a person has more independence in ADL.…”
Section: Primary Outcome Measurementioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast with findings in some other UK-based cluster randomised care home studies, which have found intracluster correlation coefficients in the range 0.37 to 0.49 for some outcome measures. 86,215 These intracluster correlation coefficients were, however, for measures such as the Barthel Index and the Rivermead Mobility Index, which were collected by independent assessors rather than directly from residents. Our largest intracluster correlation coefficient for assessment data, collected directly from residents, was 0.09 for the Short Physical Performance Battery; a larger intracluster correlation coefficient for measuring an outcome that is dependent on environmental and, possibly, assessor factors is not surprising.…”
Section: Clinical Effectivenessmentioning
confidence: 99%